Graduates’ employability: enhancing students’ overall performances / Fatin Adilah Razali ... [et al.] - Razali, Fatin Adilah; Abu Talib, Shafinaz Lyana; Awang, Naqiah (Universiti Teknologi MARA, Kedah, 2021)
This paper aims to identify the employability factors emphasised by the future employers as well as higher education institutions. The factors mostly indicate the importance of balance between students’ overall performance in both academic (technical academic ability) and non academic (soft skills) performances. This paper is based on secondary data from past literature on graduates’ employability factors, through meta-analytic approach. The model was developed based on prior researches on employability factors and it focuses on how to stimulate students’ overall performance. The L.E.A.S. (Learning, Exposure, Assimilate and Stimulate) model was developed to balance academic and non academic performances hence improving the graduates’ employability. This model requires participation from three main key players known as students, universities and employers in order to stimulate students’ ultimate performance.